Mathematics teachers’ online teaching experience in times of school closures: The case of Malaysia - Jiew, Fui Fong; Chin, Kin Eng; Jupri, Al (Universiti Utara Malaysia Press, 2022)
Purpose – Given that students were out of school in response to the COVID-19 pandemic public health measures, traditional teaching practices have been forced to switch to online mediated learning environments. This study represents the first research effort to capture the experience of Malaysian mathematics teachers about their teaching during the pandemic. This includes investigating digital education tools mathematics teachers used, issues they encountered, and the knowledge and skills they need to improve during the enforced online teaching situation.